Technical Assistance Program as A Media to Overcome the Problem of Children’s Dyslexia in Madrasah Ibtidaiyah - Hasan Baharun; Nurhidayah Trisilia; Siti Maryam Munjiat; Bannaga Taha Al-Zubair Hussen (Al Ibtida: Jurnal Pendidikan Guru MI, 2022)
AbstractReading is an important activity in everyday life and must be mastered by children from an early age. However, many children still cannot read, especially in one of the madrasah ibtidaiyah in Probolinggo Regency, East Java which is the location of this research. This study aims to analyze the teacher's strategy in overcoming the reading problem of dyslexic children with technical guidance. This study used a phenomenological approach, where researchers try to understand the phenomena in the field through interviews, observations, and documentation. Data analysis was carried out in stages, including data collection, data reduction, data presentation, and conclusions. The results showed that the teacher's strategy in overcoming the reading problem of dyslexic children through Technical Guidance was carried out through preparation of technical assistance, implementation of technical assistance, and evaluation of technical assistance. This research has implications for the importance of the teacher's understanding of student learning characteristics from an early age so that teachers can find out the students’ various problems so that learning objectives can be achieved optimally.Keywords: technical assistance, children’s dyslexia, madrasah ibtidaiyah. AbstrakMembaca merupakan kegiatan penting dalam kehidupan sehari-hari dan harus dikuasai oleh anak-anak sejak dini, namun masih banyak anak-anak yang belum bisa membaca, terutama di salah satu madrasah ibtidaiyah di Kabupaten Probolinggo, Jawa Timur yang menjadi lokasi penelitian ini. Penelitian ini bertujuan untuk menganalisis tentang strategi guru dalam mengatasi masalah membaca anak disleksia dengan bimbingan teknis. Penelitian ini menggunakan pendekatan fenomenologis, di mana peneliti mencoba memahami fenomena yang terjadi di lapangan melalui wawancara, observasi, dan dokumentasi. Analisis data dilakukan secara bertahap, mulai dari pengumpulan data, reduksi data, penyajian data, dan penarikan kesimpulan. Hasil penelitian menunjukkan bahwa strategi guru dalam mengatasi masalah membaca anak disleksia melalui Bimbingan Teknis yang dilakukan dengan penyusunan bantuan teknis, pelaksanaan bantuan teknis, dan evaluasi bantuan teknis. Penelitian ini berimplikasi pada pentingnya pemahaman guru terhadap karakteristik belajar siswa sejak dini, sehingga guru dapat mengetahui berbagai permasalahan yang akan dihadapi oleh siswa, sehingga tujuan pembelajaran dapat tercapai secara optimal.Kata Kunci: bimbingan teknis, anak-anak disleksia, madrasah ibtidaiyah.